2021
DOI: 10.1101/2021.11.11.21266068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased risk of SARS-CoV-2 reinfection associated with emergence of Omicron in South Africa

Abstract: Objective: To examine whether SARS-CoV-2 reinfection risk has changed through time in South Africa, in the context of the emergence of the Beta, Delta, and Omicron variants Design: Retrospective analysis of routine epidemiological surveillance data Setting: Line list data on SARS-CoV-2 with specimen receipt dates between 04 March 2020 and 27 November 2021, collected through South Africa's National Notifiable Medical Conditions Surveillance System Participants 2,796,982 individuals with laboratory-confirmed S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
524
2
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(565 citation statements)
references
References 26 publications
23
524
2
4
Order By: Relevance
“…It is also noteworthy that a recent retrospective study based on the population-wide epidemiological data in South Africa indicates an increased risk of SARS-CoV-2 reinfection associated with Omicron. 11 The possibility of a new wave of COVID-19 epidemic in South Africa and even around the world therefore should not be ignored.…”
Section: Characteristics Of Omicron Variantmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also noteworthy that a recent retrospective study based on the population-wide epidemiological data in South Africa indicates an increased risk of SARS-CoV-2 reinfection associated with Omicron. 11 The possibility of a new wave of COVID-19 epidemic in South Africa and even around the world therefore should not be ignored.…”
Section: Characteristics Of Omicron Variantmentioning
confidence: 99%
“…It has been reported that the increased risk of SARS-CoV-2 reinfection is associated with the emergence of the Omicron variant in South Africa, indicating that the Omicron variant may be associated with substantial ability to evade immunity from prior infection. 11 Moreover, whether the current COVID-19 vaccines can protect against the Omicron variant attracts much attention. The most recent evidence showed that the current COVID-19 vaccines provided less immunity to the omicron variant than other VOCs.…”
Section: Developing Variant-specific Vaccinesmentioning
confidence: 99%
“…Scientists from South Africa have shared their belief that prior infection with COVID‐19 provides relatively little immune protection against subsequent infection with the Omicron variant. 30 Fortunately most of the anecdotally reported Omicron cases thus far have had relatively mild symptoms and clinical manifestations. Vaccine manufacturers rapidly launched major efforts to create mRNA vaccines modified to be effective against the Omicron variant, but it is too early to be able to assess the immune response and/or protective efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific community knows little about Omicron's infectivity, vaccine breakthrough, and antibody resistance, and reliable experimental results from labs will take a few weeks to come out. Although conclusive immunological and clinical data are not yet available, early genomic data show immune evasion capabilities, fast transmission ability, reinfection rate, and severity [ 7 ]. This has triggered the calls to intensify vaccination programmes, including booster doses [ 8 ].…”
mentioning
confidence: 99%